Topical Nanoemulsion of Rifampicin with Benzoic Acid and Salicylic Acid: Activity Against Staphylococcus aureus, Stap. epidermis and Candida albicans (Bangladesh Pharmaceutical Journal, 2019)
The aim of this study was to formulate a topical nanoemulsion which can be used to treat both bacterial and fungal infections of the skin. Eight self-emulsifying drug delivery systems composed of different combinations of rifampicin (1%), benzoic acid (6%) and salicylic acid (3%) were formulated and designated as F1, F2, F3, F4, F5, F6, F7 and F8. Nanoemulsions of the eight formulations were prepared using oleic acid, Tween 80 and water by sonication method. Antibacterial and antifungal effects were observed against Staphylococcus aureus, Stap. epidermis and Candida albicans by the Kirby-Bauer method. The nanoemulsion containing only rifampicin showed strong activity against S. aureus and S. epidermis, but not against C. albicans. The nanoemulsion containing both benzoic acid and salicylic acid showed better activity in C. albicans, but not against S. aureus and S. epidermis. However, the nanoemulsions consisting of all three active ingredients showed significant results against S. aureus, S. epidermis and C. albicans.Bangladesh Pharmaceutical Journal 22(1): 1-6, 2019